THE ANALYSIS OF APPLYING QUESTION-MAKING TASK TO COMPREHEND TOEFL SUBJECTS - Nur'afifah Hasbi Nasution (Universitas Potensi Utama, 2018)
TOEFL (Test of English as Foreign Language) is widely used to measure one’s ability in English. In fact, learning TOEFL is always by answering questions. Whatever the subjects (listening, structure, error analysis or reading), students will be faced on a lot of questions. In many cases, students were tired and bored of answering questions. They even did not comprehend the subjects. To solve that problem, applying question-making task can be a solution. This study explained how the task improved students’ comprehension on TOEFL subjects. Furthermore, the task would build students’ motivation to involve in teaching-learning process. This study was also focused on exploring the result of applying question-making task as a TOEFL teaching tool. The aim of this study is to introduce TOEFL teaching technique that could enable students to comprehend TOEFL subjects. In addition, by making their own questions would motivate them to be involved in learning process.